PERTIMBANGAN HAKIM TERHADAP HAL YANG MEMBERATKAN PADA TINDAK PIDANA PENGANIAYAAN YANG MENGAKIBATKAN LUKA BERAT - Simamora Manalu, Marco Yoel; Aldyan, Arsyad (Sebelas Maret University, 2022)
In an era such today, crimes have increased. Crimes happened as the result of imbalance between human rights and their responsibility as a part of humanity. The damages cause by crimes that'd done by people can be whether its material or immaterial. One of the most famous form of crime that's quite known by people is a crime that involves human bodies. One of the example for that would be persecution. This study's aim in the writing is to analyze the judge's legal considerations in imposing a sentence of imprisonment of 8 (eight) months. The type of research used is normative legal research which is prescriptive and applied. This legal research approach uses a case approach. The legal materials used consist of primary legal materials and secondary legal materials. The legal material collection technique used is library research. The legal material analysis technique used in writing this law is the syllogism method with deductive thinking patterns. Based on the results of the research and discussion, it was concluded that the judge in making a decision complied with the Criminal Procedure Code in considering the juridical and non[1]juridical aspects of the offender.Keyowrds: Aggravating Circumstances ; Judge's Consideration ; Persecution Crime